Integrating the data. Practices of people through lithic, anthracological and zooarchaeological evidences recovered in Sector B of the ADR site (Córdoba, Argentina) - Costa, Thiago; Robledo, Andrés; Caminoa, José (Revista Chilena de Antropología, 2017)
This paper presents the integration of lithic technology, anthracological and zooarchaeological analyzes in sector B of the site Alero Deodoro Roca, located in the Sierras Pampeanas Australes, Córdoba, Argentina. It aims to compare the assemblages recovered in ADR to infer about the practices that connected people to these materials during the ca. 2970 years AP. Statistical tools were used to analyze the ubiquity, taxonomic richness and spatial distribution of material culture in the excavated sectors. Our results allow us to infer about general strategies of gathering and use of firewood, a hunting practice focused in guanacos and the presence of lithic material associated with the hunting and processing of other materials (like bones and woods). The quantitative integration of these lines of evidence together with the analysis of intrasite spatial distribution allows us to have a more complete view of the possible activities carried out in the ADR at a particular moment.